2022
DOI: 10.3389/fmed.2021.788687
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Signatures of Type 2 Diabetes Mellitus and Hypertension in COVID-19 Patients With Different Disease Severity

Abstract: Introduction: Increased COVID-19 disease severity is higher among patients with type 2 diabetes mellitus and hypertension. However, the metabolic pathways underlying this association are not fully characterized. This study aims to identify the metabolic signature associated with increased COVID-19 severity in patients with diabetes mellitus and hypertension.Methods: One hundred and fifteen COVID-19 patients were divided based on disease severity, diabetes status, and hypertension status. Targeted metabolomics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…It has rapidly become a global epidemic and a serious health threat (1). Currently, several studies have shown that some susceptible populations include type 2 diabetes, obesity, hypertension, and other metabolic diseases (2)(3)(4)(5). However, thyroid disease is not covered in the report.…”
Section: Introductionmentioning
confidence: 99%
“…It has rapidly become a global epidemic and a serious health threat (1). Currently, several studies have shown that some susceptible populations include type 2 diabetes, obesity, hypertension, and other metabolic diseases (2)(3)(4)(5). However, thyroid disease is not covered in the report.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the impact of BCG vaccinations seems to be largely hypothetical or non-specific in decreasing the severity of COVID-19 infection. Our previous study suggested a difference in the metabolic signature of Type 2 diabetic patients with COVID-19 infection compared to non-diabetic population (20). In general, diabetic patients are at a greater risk of disease progression when infected with SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 96%
“…Meanwhile, individual with severe COVID-19 show elevated plasma triglycerides (TGs), ceramides (Cer), and phosphatidylethanolamines (PEs), alongside a reduction in PCs and Lysophosphatidylcholines (LPCs), particularly LPC 20:1 [ 22 ]. Furthermore, the severity of COVID-19 in diabetic and hypertensive patients has been linked to long-chain polyunsaturated fatty acids (n3 and n6) [ 23 ]. More notably, research recognizes that certain ACE2 variants increase the binding affinity to the spike protein therefore leading to more severe infections [ 24 ].…”
Section: Introductionmentioning
confidence: 99%